Criminal Justice Systems’ Role in Crime Control in the Hashemite Kingdom of Jordan: The Public Security Agency as a Case Study - Abdel-Mawajdeh, Murad Abdullah (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to underline the role of criminal justice systems in crime control in the Hashemite Kingdom of Jordan, using the Public Security Agency as a case study. Methods: The study adopts a content analysis approach to analyze the data which was collected by interviewing several employees of the Public Security Agency. A questionnaire was designed, questions were asked to respondents, and answers were documented. The study sample consisted of officers pursuing a master’s degree at the Royal Police Academy for the academic year (2020-2021). Participants were intentionally selected from various public security departments and different military ranks. The number of officers reached (45). Results: The study shows that the judicial work done by the Public Security Agency is ranked first in crime control by criminal justice systems. The administrative and social work comes in second place whereas the reform and rehabilitation work occupy the third place. Moreover, the study reveals that there are no differences in the participants’ responses due to the number of service years or because of judicial, administrative, social, or reform and rehabilitation jobs. Conclusions: The study recommends the adequate training of workers in the field of reform and rehabilitation to enable them to work professionally in these centers. It advocates the development and implementation of aftercare programs in partnership with the concerned authorities to help in reducing recidivism after the inmate leaves the reform and rehabilitation center.